2018
DOI: 10.1186/s13256-018-1768-y
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Eales’ disease post-partum and long-term follow-up: a case report

Abstract: BackgroundEales’ disease is a difficult to treat idiopathic form of retinal vasculitis. We present such a case with peculiar epidemiology in which the only efficient therapeutic approach in order to maintain functional vision was repeated intravitreal dexamethasone implants (Ozurdex®). To the best of our knowledge this is the first report of this kind in the literature.Case presentationThis is the case of a 40-year-old white woman presenting in 2008 with recurrent floaters accompanied by blurring of vision in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Ivanescu et al described the case of a 40-year-old woman diagnosed with bilateral Eales disease whose condition rapidly worsened postpartum, with recurrent vitreous hemorrhages and a limited response to systemic treatment. In this case, the disease was controlled using intravitreal sustained-release dexamethasone implants (Ozurdex) [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ivanescu et al described the case of a 40-year-old woman diagnosed with bilateral Eales disease whose condition rapidly worsened postpartum, with recurrent vitreous hemorrhages and a limited response to systemic treatment. In this case, the disease was controlled using intravitreal sustained-release dexamethasone implants (Ozurdex) [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of choice in more advanced cases when the disease is in the proliferative stage is laser photocoagulation [ 13 , 14 ]. The aim of the laser treatment is to induce the regression of neovascularization in the areas of retinal non-perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…The management of Eales disease is based on its stage. 7 Steroids are the primary agents used most frequently in the inflammatory stage, 8,9 whereas photocoagulation is the mainstay treatment in the ischemic and neovascularization stage. 10 It is reported that retinal ischemic stimulates the production of vascular endothelial growth factor (VEGF), which leads to neovascularization and fibrous proliferation.…”
mentioning
confidence: 99%